Cognitive poetics: theoretical foundations and analytical tools in the interpretation of literary texts - Marta SEVERIN (Dialogica: Revistă de Studii Culturale și Literatură)
The aim of this paper is to define and illustrate the concepts and tools of cognitive poetics – a new way of analyzing and interpreting a literary text that focuses on the effects of a read text on the reader’s mind, as well as the cognitive processes that occur in response to the reading experience. Department cognitive poetics aims, therefore, at the relationship between writer, the literary text and its effects on reader’s mind. The reader anchors himself in the text thanks to the spatio-temporal deictic elements provided by the writer, selects the predominant elements of the text and reliefs the textual worlds, establishes an indissoluble link between reality and literary space through the prism of his experience and, according to this experience, is able to denounce the figurative meaning of the conceptual metaphor. Cognitive poetics, through these tools, succeeds in establishing the cognitive processes of the reader who is summoned to discover the „proper” world of the text.